2019
DOI: 10.3390/plants8050137
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Promotes Agronomic Performance in Brassica napus Cultivated under Field Conditions with Two Nitrogen Fertilizer Inputs

Abstract: To limit the environmental pollution associated with intensive nitrogen (N) fertilizer usage, alternative cultural practices must be considered for crops requiring high N inputs such as rapeseed. In this context, the effects of silicon (Si) supply on the agronomic performance of rapeseed cultivated under field conditions with two N fertilizer levels (60 and 160 kg ha−1) were studied. Results showed that Si supplied in the form of silicic acid (12 kg ha−1) has no effect on the agronomic performance of plants cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Most importantly, the application of Si in the present study exhibited no negative affection on the main agronomic traits and seed quality of rapeseed. This is in accordance with studies in which Si was found to protect plants against many biotic and abiotic stresses without the occurrence of resistance trade-offs and/or growth and yield penalties (Fauteux et al, 2005 ; Ma and Yamaji, 2006 ; Laîné et al, 2019 ). Therefore, Si application may provide a new protective strategy to control SSR in rapeseed.…”
Section: Discussionsupporting
confidence: 91%
“…Most importantly, the application of Si in the present study exhibited no negative affection on the main agronomic traits and seed quality of rapeseed. This is in accordance with studies in which Si was found to protect plants against many biotic and abiotic stresses without the occurrence of resistance trade-offs and/or growth and yield penalties (Fauteux et al, 2005 ; Ma and Yamaji, 2006 ; Laîné et al, 2019 ). Therefore, Si application may provide a new protective strategy to control SSR in rapeseed.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, protein hydrolysates are known to have biostimulant properties under field conditions, such as in tomatoes (Polo and Mata, 2017). Finally, other kinds of biostimulants, such as silicon, may enhance yield and seed quality under field conditions, but only under high N fertilization (Laîné et al, 2019). Altogether, these results demonstrated that VNT4 mixed with N fertilizer has a significant impact on yield and NUE, especially when mixed with UAN, which confirmed the results obtained under greenhouse conditions.…”
Section: Vnt4 Increased Yield and Nue Under Field Conditionssupporting
confidence: 80%
“…One explanation could be that Si mediates increase in cytokinin activity in the leaf N source/sink balance via the increased expression of the gene CWINV1 encoding β-fructofuranosidase, insoluble isoenzyme 1 (Markovich et al, 2017). Silicon fertilization is known to improve N use efficiency and agronomic parameters of crops (yield and nutritional value) as observed in the long-term experiments in rice (Cuong et al, 2017), maize (Mabagala et al, 2020), rapeseed (Laine et al, 2019), and wheat (Triticum aestivum) (Neu et al, 2017). Although the underlying mechanism has not been studied in detail, it has been demonstrated that Si-induced biosynthesis of amino acids and remobilization of N (Detmann et al, 2012) can partially explain this phenomenon.…”
Section: Conditionsmentioning
confidence: 99%